A method for reconstructing the internal morphological structure of wheat kernels upon Sitophilus zeamais infestation. (September 2020) - Zhou, Ying; Hui, Yan-Bo; Feng, Lan-Fang; Zhou, Tao; Wang, Qiao
Abstract: Weevils ( Sitophilus zeamais ) are the most harmful stored-grain pest, and they appear as damage inside wheat kernels. The morphological changes to the inner kernel structure that occur after weevil infestation have not been thoroughly studied. Rapid and non-destructive methods for studying weevil damage would be readily accepted by the grain storage and quality control industry. Traditional research methods for investigating the morphological structures of kernels are mostly destructive and two-dimensional (2D) and cannot provide information on the three-dimensional (3D) spatial structure inside a kernel in a non-destructive and complete manner. X-ray Micro-Computed Tomography (X-ray μCT), a non-destructive 3D imaging and analysis technique used for studying the internal structure of a variety of materials, has great potential for application in the field of cereal science. To this end, this study involved a non-destructive imaging method based on X-ray μCT for measuring and characterizing the morphological structure of wheat kernels infested with S. zeamais . Through this method, X-ray μCT was used to acquire high-resolution 2D tomographic images (referred to here as 2D slices), which were subjected to noise reduction, filtering, segmentation, and reconstruction for the 3D visualization of the morphological structure inside S. zeamais -infested wheat kernels. A quantitative analysis of key parameters reflecting the changes in the morphological structure was also performed. The following results were obtained: (1) Based on differences in grayscale values in the 2D slices, the complex anatomical features inside the kernels were distinguished, and patterns of change in the components inside the kernels were determined successfully. (2) Using a 3D visualized characterization of the morphological structure, detailed spatial descriptions of the structural damage inside S. zeamais -infested kernels were achieved when S. zeamais was at different life stages. (3) A quantitative analysis was performed on the changes in key parameters in specific tissues inside S. zeamais -infested wheat kernels at different stages. As S. zeamais development progressed, certain insect parameters and the holes in the kernels caused by the S. zeamais feeding processes inside the kernel increased. The changes were particularly notable at 22 d of S. zeamais development, when the hole accounted for approximately 21% of the entire wheat kernel. Highlights: X-ray Micro-Computed Tomography was used to nondestructive characterize and quantify the internal structure of wheat kernels upon Sitophilus zeamais Infestation. Image analysis algorithm was used to noise reduction, filtering, segmentation, and reconstruction for 3D visualization of the morphological structure. Quantitative analysis brings the necessary information to understand the real changes in the morphological structure parameter of Sitophilus zeamais and holes.